2020
DOI: 10.1515/ncrs-2020-0511
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of bi-1,1′-cyclopentane-1,1′-diol, C10H18O2

Abstract: C10H18O2, monoclinic, C2/c (no. 15), a = 10.0025(5) Å, b = 18.8285(9) Å, c = 11.2384(6) Å, β = 115.327(2)°, V = 1913.11(17) Å3, Z = 8, Rgt(F) = 0.0596, wRref(F2) = 0.1606, T = 200 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…To allow for comparisons of metrical parameters of the title compound in envisioned coordination compounds, the crystal and molecular structure of the free ligand was determined. The crystal structures of the related pinacols derived from cyclopentanone (Hosten & Betz, 2021), cycloheptanone (Betz & Klu ¨fers, 2007) and cyclododecanone (Yang et al, 2016) are apparent in the literature. Structural data of symmetric pinacols derived from methyl-substituted (Bruss et al, 1987) and phenyl-substituted cyclohexanones (Nieger et al, 2004) have been reported.…”
Section: Structure Descriptionmentioning
confidence: 99%
“…To allow for comparisons of metrical parameters of the title compound in envisioned coordination compounds, the crystal and molecular structure of the free ligand was determined. The crystal structures of the related pinacols derived from cyclopentanone (Hosten & Betz, 2021), cycloheptanone (Betz & Klu ¨fers, 2007) and cyclododecanone (Yang et al, 2016) are apparent in the literature. Structural data of symmetric pinacols derived from methyl-substituted (Bruss et al, 1987) and phenyl-substituted cyclohexanones (Nieger et al, 2004) have been reported.…”
Section: Structure Descriptionmentioning
confidence: 99%